Environmental controls on bacteriohopanepolyol profiles of benthic microbial mats from Lake Fryxell, Antarctica. Issue 5 (19th July 2019) - Matys, Emily D.; Mackey, Tyler; Grettenberger, Christen; Mueller, Elliott; Jungblut, Anne; Sumner, Dawn Y.; Hawes, Ian; Summons, Roger E.
Abstract: Bacteriohopanepolyols (BHPs) are pentacyclic triterpenoid lipids that contribute to the structural integrity and physiology of some bacteria. Because some BHPs originate from specific classes of bacteria, BHPs have potential as taxonomically and environmentally diagnostic biomarkers. For example, a stereoisomer of bacteriohopanetetrol (informally BHT II) has been associated with anaerobic ammonium oxidation (anammox) bacteria and suboxic to anoxic marine environments where anammox is active. As a result, the detection of BHT II in the sedimentary record and fluctuations in the relative abundance of BHT II may inform reconstructions of nitrogen cycling and ocean redox changes through the geological record. However, there are uncertainties concerning the sources of BHT II and whether or not BHT II is produced in abundance in non‐marine environments, both of which are pertinent to interpretations of BHT II signatures in sediments. To address these questions, we investigate the BHP composition of benthic microbial mats from Lake Fryxell, Antarctica. Lake Fryxell is a perennially ice‐covered lake with a sharp oxycline in a density‐stabilized water column. We describe the diversity and abundance of BHPs in benthic microbial mats across a transect from oxic to anoxic conditions. Generally, BHP abundances and diversity vary with the morphologies of microbial mats, which were previously shown to reflect local environmental conditions, such as irradiance and oxygen and sulfide concentrations. BHT II was identified in mats that exist within oxic to anoxic portions of the lake. However, anammox bacteria have yet to be identified in Lake Fryxell. We examine our results in the context of BHPs as biomarkers in modern and ancient environments.